B‐cell lymphoma/leukaemia 11B (BCL11B) expression status helps distinguish early T‐cell precursor acute lymphoblastic leukaemia/lymphoma (ETP‐ALL/LBL) from other subtypes of T‐cell ALL/LBL. (16th August 2021) - Fang, Hong; Wang, Wei; El Hussein, Siba; Morita, Kiyomi; Beird, Hannah C.; Mitra, Akash; Loghavi, Sanam; Lin, Pei; Jabbour, Elias J.; Khoury, Joseph D.
Summary: B‐cell lymphoma/leukaemia 11B (BCL11B) is an essential transcription factor for T‐cell lineage commitment and maturation. We investigated BCL11B expression by immunohistochemistry in T‐lymphoblastic leukaemia/lymphoma (T‐ALL/LBL) ( n  = 115). The majority (83%) of early T‐cell precursor T‐ALL/LBL (ETP‐ALL) cases showed negative BCL11B expression, while most (84%) of non‐ETP‐ALL/LBL were positive for BCL11B. A simplified three‐marker [BCL11B, cluster of differentiation 5 (CD5), CD13] immunophenotypic score discriminated reliably between ETP‐ALL and non‐ETP‐ALL/LBL. In ETP‐ALL, patients with positive BCL11B expression had a better overall survival than those with negative BCL11B ( P  = 0·009). In summary, BCL11B is a valuable marker for T‐ALL/LBL subtyping and serves as a potential prognostic marker in patients with ETP‐ALL.